2014
DOI: 10.1128/jvi.01024-14
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Covalently Closed Circular Hepatitis B Virus DNA Induces Prolonged Viral Persistence in Immunocompetent Mice

Abstract: It remains crucial to develop a laboratory model for studying hepatitis B virus (HBV) chronic infection. We hereby produced a recombinant covalently closed circular DNA (rcccDNA) in view of the key role of cccDNA in HBV persistence. A loxP-chimeric intron was engineered into a monomeric HBV genome in a precursor plasmid (prcccDNA), which was excised using Cre/loxPmediated DNA recombination into a 3.3-kb rcccDNA in the nuclei of hepatocytes. The chimeric intron was spliced from RNA transcripts without interrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 36 publications
2
105
0
Order By: Relevance
“…An in vivo model based on hydrodynamic injection in which an exogenous gene was expressed long-term was first constructed for non-HBV research [15, 35]. Models were then established using the same method to study HBV infection [4, 7, 12, 16, 20, 29, 33, 36]. In this study, we introduced HBV DNA into mouse livers by hydrodynamic injection.…”
Section: Discussionmentioning
confidence: 99%
“…An in vivo model based on hydrodynamic injection in which an exogenous gene was expressed long-term was first constructed for non-HBV research [15, 35]. Models were then established using the same method to study HBV infection [4, 7, 12, 16, 20, 29, 33, 36]. In this study, we introduced HBV DNA into mouse livers by hydrodynamic injection.…”
Section: Discussionmentioning
confidence: 99%
“…We found that when each combined with Cas9, several sgRNAs efficiently diminished HBV protein production as measured by ELISA of HBV surface antigen (HBsAg) ( Figure 1B). We also performed T7E1 assays in a cell model that produces episomal HBV cccDNA [14], and found that together with Cas9, all sgRNAs except for B9 induced indels in the HBV DNA ( Figure 1C). We selected the most potent sgRNA B5 (sgB5) based on its performance in ELISA for further analysis.…”
Section: Dear Editormentioning
confidence: 99%
“…The drawback of this approach is the low DNA yield and need for extra steps of DNA manipulation prior to each transfection experiment. Another ingenious method is to use a specialized cloning vector which can be removed inside transfected cells through Cre/loxP-mediated DNA recombination, thus generating authentic cccDNA-like molecules inside cells (Qi et al, 2014). Alternatively, 1.1 copies of terminally redundant HBV DNA that covers the entire length of pg RNA can be inserted to an expression vector downstream of the strong CMV promoter to drive extremely high level of pg RNA transcription and genome replication (Junker et al, 1987).…”
Section: Discussionmentioning
confidence: 99%